Moringa Bean Cake as A Ready to Use Therapeutic (RUTF) Ingridient in Malnourished Children Aged 12-59 Months in Maluku Province: A Multicenter Project - Sri Wahyuni Djoko (Postgraduate, University of Mataram, 2025)
Nutritional status of toddlers is a description of the nutritional status of the community that affects the low quality of human resources. Nutritional problems arise if the intake of nutrients consumed does not match nutritional needs. To analyze the effect of giving moringa bean cookies as a Ready to Use Therapeutic Food (RUTF) ingredient on weight gain in children with undernutrition aged 12-59 months in Maluku Province in 2023. This study is quasi-experimental analysis research with interrupted time series design, with population in inclusion criteria is children with malnutrition aged 12-59 months and do not have peanut allergy, the weight measured taken before and after intervention to observe the impact from RUTF. A sample of 56 children divided into treatment group and control group. Statistical analysis uses bivariate dependent t-test. Result for this study, showed that there was a significant effect of RUTF on the weight of malnourished children aged 12-59 months (p=0.000). The average weight of toddlers before the administration of RUTF (10.22 Kg) and after the administration of RUTF (11.67 Kg) with a P-value of 0.000, but there is no significant difference between intervention and control groups. Which p value is 0.25.